Literature Study: ICT-Based IPS-PKN Learning Design in Elementary School - Rati Syafiana Putri; Yeni ERITA; Wiwit SANJAYA; SALMIYANTI (RADINKA JAYA UTAMA PUBLISHER, 2022)
Learning social studies and Civics is very much a practice in life, so it must be well designed and adapted to technological developments. This study aims to analyze the ICT-based conception of IPS-Civics in elementary schools. This research is a literature review in the form of ICT studies in Social Sciences and Civics learning at schools which are published in national journals or reports. The conclusion of research on the use of ICT in education is important to support educational processes and outcomes. As educational implementers, teachers need to design the learning process by creating the right atmosphere so that the learning process runs effectively, efficiently and interestingly. ICT in elementary schools must be developed by teachers in the learning processtoprovide meaningful and enjoyable learning each student. Keywords: Learning design, IPS and Civics, ICT